Stakeholder Engagement: Analyzing the Role of Community Participation in EIA Document Crafting for PT Semen Indonesia's Cement Plant - Leony Fatmawati; Hufron Hufron; Ievgenii Shulga (Mimbar Keadilan, 2024)
This study aims to clarify the community involvement process in preparing AMDAL papers for the construction of a cement plant by PT Semen Indonesia (Persero) Tbk in Rembang Regency, Central Java Province. An Environmental Impact Assessment (AMDAL) document is mandatory for any development and mining operation and must be prepared by the party responsible. The community's involvement in decision-making and evaluation stages is crucial for the construction site. This research utilizes a normative technique incorporating a statutory, conceptual, and case-based approach. The findings illustrate community engagement through their involvement in preparing AMDAL papers. This study investigates the level of community engagement in preparing Environmental Impact Assessment (EIA) reports for establishing a cement factory by PT Semen Indonesia (Persero) Tbk in Rembang Regency, Central Java Province. Furthermore, it examines the disputes between PT Semen Indonesia (Persero) Tbk and the local community on regulating community involvement in preparing the Environmental Impact Assessment (EIA) document